2019
DOI: 10.21873/anticanres.13269
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Assessment of Carbon-ion Beam Radiotherapy: A Systematic Review of Clinical Effectiveness and Safety for 54 Oncological Indications in 12 Tumour Regions

Abstract: Background/Aim: Due to the unique physical dose distribution of carbon-ion radiotherapy (CIRT), CIRT can be regarded as a novel tumour irradiation technique-potentially advantageous for various tumour types. Yet it is unclear in how far, superiority or inferiority can be claimed when comparing CIRT to standard irradiation. This study aimed to assess the scientific evidence regarding the effectiveness and safety of CIRT. Materials and Methods: A systematic literature review was performed using the European Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Only English language publications were included in our systematic review, and important studies may have been excluded. Our conclusions regarding CIT concur with Goetz et al 62 that though CIT is a promising cancer treatment, neither superiority or inferiority can be claimed when compared to conventional treatment options. The unique biological as well as physical properties of carbon ions mean that CIT needs to be integrated into translational treatment programs in novel ways in order to exploit their maximum potential such as eliciting an enhanced immune response.…”
Section: Discussionsupporting
confidence: 90%
“…Only English language publications were included in our systematic review, and important studies may have been excluded. Our conclusions regarding CIT concur with Goetz et al 62 that though CIT is a promising cancer treatment, neither superiority or inferiority can be claimed when compared to conventional treatment options. The unique biological as well as physical properties of carbon ions mean that CIT needs to be integrated into translational treatment programs in novel ways in order to exploit their maximum potential such as eliciting an enhanced immune response.…”
Section: Discussionsupporting
confidence: 90%
“…Until 2016, approximately 21,580 patients were recorded to have been treated with CIRT internationally. 8 For ocular tumors, CIRT has been delivered to choroidal melanoma and lacrimal gland tumors with an acceptable morbidity and sufficient local control, but experience is very limited. [9][10][11] Key Structures, Dose Tolerance, and Toxicity…”
Section: Carbon Ion Radiotherapymentioning
confidence: 99%
“…Medium-sized melanomas with a height of less than 8 mm and a diameter of less than 16 mm can be treated with I-125 brachytherapy (minimum tumor dose of 85 Gy) and proton radiotherapy (►Figs. [7][8][9][10] with eye preservation or enucleation, Interestingly, no difference in mortality has been observed between patients with medium-sized melanomas treated with brachytherapy versus enucleation. 48 Furthermore, high-dose radiation therapy for uveal melanomas has shown comparable survival outcomes to those of surgery.…”
Section: Managementmentioning
confidence: 99%
“…The authors acknowledge that although the current clinical evidence supporting the use of carbon ion therapy is compelling, it is incomplete . The pioneering investigations at LBNL showed that fractionated delivery of heavy ion therapy, generally as a boost at relatively low doses, was well tolerated across diverse tumor sites, including locally advanced prostate cancer, bone and soft tissue sarcomas, and head and neck tumors of the salivary gland and paranasal sinus .…”
Section: Opening Statementsmentioning
confidence: 99%